Quinoa Seed Quality Response to Sodium Chloride and Sodium Sulfate Salinity - Wu, Geyang; Peterson, Adam J.; Morris, Craig F.; Murphy, Kevin M. (Frontiers in Plant Science, 2016)
Quinoa (Chenopodium quinoa Willd.) is an Andean crop with an edible seed that both contains high protein content and provides high quality protein with a balanced amino acid profile in embryonic tissues. Quinoa is a halophyte adapted to harsh environments with highly saline soil. In this study, four quinoa varieties were grown under six salinity treatments and two levels of fertilization, and then evaluated for quinoa seed quality characteristics, including protein content, seed hardness, and seed density. Concentrations of 8, 16, and 32 dS m-1 of NaCl and Na2SO4, were applied to the soil medium across low (1 g N, 0.29 g P, 0.29 g K per pot) and high (3 g N, 0.85 g P, 0.86 g K per pot) fertilizer treatments. Seed protein content differed across soil salinity treatments, varieties, and fertilization levels. Protein content of quinoa grown under salinized soil ranged from 13.0% to 16.7%, comparable to that from non-saline conditions. NaCl and Na2SO4 exhibited different impacts on protein content. Whereas the different concentrations of NaCl did not show differential effects on protein content, the seed from 32 dS m-1 Na2SO4 contained the highest protein content. Seed hardness differed among varieties, and was moderately influenced by salinity level (P = 0.09). Seed density was affected significantly by variety and Na2SO4 concentration, but was unaffected by NaCl concentration. The samples from 8 dS m-1 Na2SO4 soil had lower density (0.66 g/cm3) than those from 16 dS m-1 and 32 dS m-1 Na2SO4, 0.74 and 0.72g/cm3, respectively. This paper identifies changes in critical seed quality traits of quinoa as influenced by soil salinity and fertility, and offers insights into variety response and choice across different abiotic stresses in the field environment.